High-Speed Camera Observation of Coal Combustion in Air and O2/CO2 Mixtures and Measurement of Burning Coal Particle Velocity - Zhang, L.; Binner, E.; Qiao, Y.; Li, Chun-Zhu (American Chemical Society, 2010)
An advanced high-speed camera with a spatial resolution of 20 μm and time scale of 1−2 ms was employed to observe coal particle combustion in a laboratory-scale drop-tube furnace (DTF). Dynamic information, including burning coal particle velocity and its residence time, was also obtained through analysis of multiple exposures. Two coal samples (bituminous coal and brown coal) and a char of the bituminous coal were burnt at 1000 °C in both air and two O2/CO2 mixtures. The coal particle size was restricted to 106−153 μm. The results indicated the obvious variation of particle motion with reactor height, coal type, and gas atmosphere. Volatiles released at the initial stage of bituminous coal combustion greatly reduced the particle falling velocity, because of the formation of a large buoyant force in the vicinity of particles. Such a phenomenon was however not observed for the brown coal with an abundance of volatile matter.Gaseous species were preferentially ejected during brown coal pyrolysis, which rapidly escaped from the particle surface. A backward momentum could even be formed to accelerate particle falling. The consumption/combustion rate of the released volatiles from bituminous coal further played an important role on the particle motion in the late stages. Replacement of air with 21% O2/79% CO2 increased the duration of volatile consumption on the particle surface, thus slowing particle motion over a relatively long period. Increasing the O2 fraction in CO2 fastened the volatile consumption rate. The particle velocity was improved consequently. These findings were not predicted by a conventional nonreacting particle motion model, bearing significance for understanding the kinetics of pulverized coal combustion as well as retrofitting of existing power generation plants with an oxy-fuel combustion technology that burns coal in an O2/CO2 mixture.